Effects of omega-3 polyunsaturated fatty acids supplements on psychopathology and metabolic parameters in schizophrenia: A meta-analysis of randomized controlled trials - Goh, Kah K; Chen, Cynthia Yi-An; Chen, Chun-Hsin; Lu, Mong-Liang (Journal of psychopharmacology (Oxford), 2021)
Several monotherapy and augmentation strategies have been introduced to improve the treatment of schizophrenia. The benefits of omega-3 polyunsaturated fatty acids in patients with mental disorders is becoming increasingly acknowledged. However, its role in the treatment of schizophrenia raises complex considerations about which there has been little consensus. The aim of this study was to synthesize the findings of randomized controlled trials that were conducted to determine the efficacy and safety of omega-3 polyunsaturated fatty acids in patients with schizophrenia. The MEDLINE, Embase, Cochrane, Scopus, and Web of Science databases were searched for relevant literature. The primary outcome was changes in psychopathology and the secondary outcomes were changes in metabolic parameters and safety profiles. Twenty double-blind randomized controlled trials in 1494 patients were included. Omega-3 polyunsaturated fatty acids augmentation was associated with significantly improved psychopathology in patients with schizophrenia, particularly general psychopathology and positive symptoms but not negative symptoms. Patients who were severely ill and received omega-3 polyunsaturated fatty acids containing eicosapentaenoic acid >1 g/d showed significant improvement. A favorable effect of omega-3 polyunsaturated fatty acids supplements on serum triglycerides was also demonstrated. Omega-3 polyunsaturated fatty acids are well-tolerated and safe in patients with schizophrenia. These findings tentatively support the use of omega-3 polyunsaturated fatty acids as a potential augmentation strategy in schizophrenia. Further research in larger samples is warranted to clarify the optimal dosage and the correct proportions of omega-3 polyunsaturated fatty acids to administer, together with elucidation of the underlying mechanisms.